Development of a HOTS Indicator Availability Test Instrument for Instructional Media - Rahmi, Miftahurrahmi; Rahim, Fanny Rahmatina; Sari, Silvi Yulia; Murtiani, Murtiani (Journal of Innovative Physics Teaching, 2024)
The 21st century demands reforms in education, especially in developing HOTS abilities. Based on observation data at SMAN Kota Padang, students' learning achievements that contain HOTS indicators have not been implemented well. The solution is to develop an instrument to test the availability of HOTS indicators in learning media. The research aims to produce an instrument for the availability of HOTS indicators in learning media. The development model for this research is the ADDIE model (analysis, design, development, implementation and evaluation). The use of the ADDIE development model is only limited to the development stage. The first stage is to conduct a needs analysis through questionnaires and interviews. The second stage is designing instrument indicators. Next, instruments are developed based on indicators. The third stage is testing the validity of the instrument. The instrument was validated by three experts from Physics lecturers at Padang State University. The results of the validity test obtained a valid instrument. Therefore, this instrument is suitable to be used to analyze the availability of HOTS indicators in the media.